THE ROLE OF FINANCIAL LITERACY IN SHAPING THE SAVINGS BEHAVIOR OF INDONESIAN MASTER VOCATIONAL SCHOOL STUDENTS - Dewi Sulistyani; Rahmatullah Rahmatullah; I Nyoman Suri Adnyana; Didi Sukardi; Murdiyono Murdiyono (Nusantara Hasana Journal, 2023)
Financial literacy is an individual's ability to understand and manage finances wisely, thus fostering positive financial behavior, including savings habits. This study aims to analyze the role of financial literacy in shaping savings behavior among students at the Indonesian Master Vocational School (SMK Master Indonesia). The research method used was a quantitative approach, with questionnaires distributed to students at the Indonesian Master Vocational School as respondents. The results showed that financial literacy positively influenced students' savings behavior. Students with a good financial understanding tended to be more disciplined in managing their pocket money and setting aside a portion of their income for savings.